Peran Mediasi Brand Image pada Pengaruh Kualitas Produk terhadap Purchase Intention Sepatu Casual Bata (Studi pada Toko Sepatu Bata di Jalan WR. Supratman Denpasar) - I Gusti Agung Made Galang Pradnya Suara1; Putu Saroyini Piartrini (Pusat Riset dan Inovasi Nasional, 2025)
The World Footwear Yearbook 2023 ranks Indonesia as the fifth-largest consumer of footwear globally, indicating that the country is one of the most promising footwear markets. Bata, once a leading brand in the Indonesian casual shoe industry, has experienced a significant decline in reputation and sales, particularly in its store on WR. Supratman Street in Denpasar. This decline is suspected to be influenced by customers’ perceptions of the product quality and the brand’s image. This study aims to investigate the relationship between the brand image of Bata casual shoes and the impact of product quality on consumers’ purchase intention. The study used purposive sampling as part of a non-probability sampling strategy, focusing on customers who had previously purchased Bata shoes at the specified store. The results indicate that product quality not only plays a crucial role in building a positive brand perception but also has a direct and significant impact on consumers’ purchase intention. Moreover, the analysis reveals that the correlation between product quality and purchase intention is largely mediated by the brand image, which has a substantial impact on increasing purchase intention. Based on these findings, it can be concluded that improving product quality standards can enhance customers’ perceptions of the Bata brand, which in turn is likely to drive higher purchase intention. Therefore, companies should focus on improving product quality and brand image management strategies to attract greater consumer interest in the Indonesian casual shoe market.